DEVELOPMENT OF MODERN DIRECTIONS OF DRIVING TRAINING AND RECOMMENDATIONS FOR INCREASING TRAFFIC SAFETY - Abdukhalil Ismoilov; Abdulatif Abdubannopov (European Science Publishing, 2023)
The article describes the process of improving the mechanism of driver training and evaluating its impact on ensuring traffic safety, as well as the implementation of modern methods of driver training
Keywords: Road, transport, passenger, road traffic accident, safety.